Continuous Lighting Promotes Plant Growth, Light Conversion Efficiency, and Nutritional Quality of Eruca vesicaria (L.) Cav. in Controlled Environment With Minor Effects Due to Light Quality - Proietti, Simona; Moscatello, Stefano; Riccio, Francesca; Downey, Peter; Battistelli, Alberto (Frontiers in Plant Science, 2021)
LEDs lamps can allow the optimization of lighting conditions in artificial growing environments, with respect to light quality, quantity and photoperiod extension, to precisely manage resources and crop performance. Eruca sativa Mill. was hydroponically cultured under three light treatments to investigate the effect on yield and nutritional properties of rocket plants. A treatment of (W-12h) having a 12/12 h light/dark at 600 µmol m−2 s−1 provided by LEDs W:FR:R:B = 12:2:71:15 was compared with two treatments of continuous lighting (CL), 24 h light at 300 µmolm−2 s−1 providing by Cool White LEDs (W-CL), and by LED R:B = 73:27 (RB-CL). CL enhanced growth of the rocket plants: total fresh biomass, leaf fresh weight, and shoot/root ratio increased in W-CL. and leaf dry weight, leaf dry matter %, root fresh and dry weight, and SLDW increased in RB-CL. Total carbon content was higher in RB-CL, whereas total nitrogen and proteins content increased in W-12h. Both W-CL and RB-CL increased carbohydrate content in rocket leaves, while W-CL alone increased the sugar content in the roots. Fibers, pigments, antioxidant compounds, and malic acid were increased by CL regardless of the light spectra applied. Nitrate was significantly reduced in rocket leaves grown both in W-CL and RB-CL. Thus, the application of CL with low light intensity can increase the yield and quality value of rocket, highlighting that careful scheduling of light spectrum, intensity and photoperiod can improve the crops performance.